Study of the Effect of the Variation Effect of Water Temperatures on Shore (D) Hardness for Some Polymers - Rasheed, Zaynab Naif (Al-Nahrain Journal of Science, 2013)
The current investigation was carried to study and determine the value of shore [D] hardness for different kinds of polymers [Epoxy [Ep], unsaturated polyester [UPE] and unplasticised PVC. After the preparation our samples Shore [D] hardness values were measured for the samples at 25 ºC. Then the samples were immersed in water bath of two types of water [distilled and tap water] at different temperatures [40,50 & 60] ºC for different times [1,2,3 & 4] hour. Other samples immersed in cooled water at 10 ºC for the same previous periods for comparing the obtained results from samples under test, it was found that the shore hardness value decreases after the immersion of samples in both types of water at 25 ºC for [1,2,3 & 4] hours, the hardness value decreased after immersing these samples in water bath at higher temperature as, while increases when the samples immersed in two types of water at 10 ºC at the same period. The obtained results showed that the rate of decreasing or increasing of hardness value depends on the period of the immersion and the type of the solution used as well as the nature of water and it’s temperature.